Perencanaan dan Perancangan Pusat Olahraga Bulutangkis di Kabupaten Buleleng Singaraja - Gede Semara Arta Arta; I Nyoman Gede Maha Putra; I Nyoman Nuri Arthana (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2022)
Badminton field is one of the facilities to accommodate several people who carry out sports activities as well as holding competitions for badminton. The Badminton Court is able to become a training ground for the younger generation who are starting to like badminton, and can further hone the skills of the young athletes candidates and open an opportunity to become Badminton Athletes. Aims as adequate facilities for a place to practice and able to accommodate the activities of badminton competitions held both at the national and international levels. The location chosen as the Badminton Court is in Buleleng Regency – Singaraja City. This location has criteria that can be considered as a place to build a badminton court. Singaraja City is an Education City, broadly speaking, there are more and more prospective young athletes who like badminton. By making this field more attractive to demand as a means for badminton, the design of the badminton court does not only provide facilities other than sports/badminton workshops, but there is a gathering place or a place to relax (communal space), food court, cafeteria, and mess . by applying the Hightech Architecture Trend, with the concept of Sportive Solidarity that attracts the attention of the public. With the context of trend development and also adapting high-tech modern architectural style.